2007
DOI: 10.1007/s10532-007-9144-4
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effect on bacterial azo bond reduction kinetics: an Arrhenius plot analysis

Abstract: Studied was the effect of temperature in the range 12-46 degrees C on the rate of bacterial decolorization of the mono-azo dye Acid Orange 7 by Alcaligenes faecalis 6132 and Rhodococcus erythropolis 24. With both strains the raise of temperature led to a corresponding raise of decolorization rate better manifested by R. erythropolis. The analysis of the Arrhenius plot revealed a break near the middle of the temperature range. The regression analysis showed practically complete identity of the observed break po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 18 publications
1
15
1
Order By: Relevance
“…This phenomenon may be the result of differences in the microbial composition between mesophilic and thermophilic sludge. Alternatively, it may also reflect a temperature-dependent change of the activation energy, similar to that observed for non-mediated azo dye reduction by two distinct pure cultures (Angelova et al, 2008). In contrast, explanations based on the release of intracellular mediators as a result of higher cell decay at higher temperatures are probably not valid: it would imply that, due to the higher pool of mediators, the impact of additional mediators is lower with sludge than with sulfide, something which is obviously not the case.…”
Section: Temperaturementioning
confidence: 73%
See 1 more Smart Citation
“…This phenomenon may be the result of differences in the microbial composition between mesophilic and thermophilic sludge. Alternatively, it may also reflect a temperature-dependent change of the activation energy, similar to that observed for non-mediated azo dye reduction by two distinct pure cultures (Angelova et al, 2008). In contrast, explanations based on the release of intracellular mediators as a result of higher cell decay at higher temperatures are probably not valid: it would imply that, due to the higher pool of mediators, the impact of additional mediators is lower with sludge than with sulfide, something which is obviously not the case.…”
Section: Temperaturementioning
confidence: 73%
“…In this study it was observed that the first-order reaction rate constant of non-mediated reduction of Reactive Red 2 (0.3 mM) by sulfide (4.5 mM) was 2.2-fold higher at 55°C than at 30°C, and AQS (12 µM) increased these rate constants 1.9-fold and 1.7fold at 30°C and 55°C, respectively (Dos Santos et al, 2004a). In biological systems, there will be limits to the temperature range of individual cultures and enzyme systems, as has been demonstrated for non-mediated azo dye reduction by several pure cultures (Chang and Kuo, 2000;Chang et al, 2001;Yu et al, 2001;Pearce et al, 2006;Angelova et al, 2008) but not for mediated azo dye reduction. Mixed cultures such as sludge will undergo population shifts when the temperature is changed.…”
Section: Temperaturementioning
confidence: 99%
“…As seen in Table 3 the optimum temperature for OM2R dye decolorization was 37°C for the AO (E. termitis) attained a maximum decolorization of 93%. Angelova et al (2008) 37 found that the azo bond reduction rate rose with an increased temperature, a maximum rate of around 40°C, 3-5 times faster than at 20°C. At 30°C and 45°C the degradation rate for OM2R by AO E. termitis was 82% and 72% of dye.…”
Section: Discussionmentioning
confidence: 99%
“…The Alcaligenes phylotype was predominant in the anaerobic parts of the investigated biofilter. Alcaligenes relatives have previously been found among microbial consortia degrading azo dyes [48]. Furthermore, the family Alcaligenaceae includes the species Pigmentiphaga , proven effective in decolorization of azo dyes [49], and has genes for at least two azoreductases [50].…”
Section: Resultsmentioning
confidence: 99%